Advances in financial economics. Vol. 15 - Ferris, Stephen P.; John, Kose; Makhija, Anil K. (Advances in financial economics., 2012)
This volume contains eight empirical papers that examine corporate governance from a number of different perspectives. Howe et al investigate how governance can influence short- and long-term performance in the case of Special Purpose Acquisition Companies; Javakhadze et al analyze limits to convergence in international corporate governance practices; Barak and Lauterbach focus on the private benefits of control; and Dong examines the relation between the discipline of options and corporate debt and the design of executive compensation. Jiang et al measure the effect of R&D expenditures on bondholders; Gondhalekar et al examine the capital market response to financial restatements; Al-Khouri reports robust evidence that privately owned banks are more risky than government-owned banks; and Luo and Jackson conclude that the positive relationship between tunneling and executive compensation implies personal benefits for controlling shareholders at the expense of minority shareholders.